2011
DOI: 10.2528/pierc11061504
|View full text |Cite
|
Sign up to set email alerts
|

Doa Estimation Using Time-Frequency Conversion Pre-Processing Method

Abstract: In many cases, the study of DOA estimation techniques is developed based on ideal condition of signal sources and array sensor antennas. But, there are much more errors as a result of signal shadow effects from noise contribution and interference of installation environment in real system. In this paper, the DOA estimation algorithm using the de-noising pre-processing based on time-frequency conversion analysis was proposed, and the performance was analyzed. This is focused on the improvement of DOA estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Far from the results in the case of using desulfurized bottom ash [6], it is concluded that neither DFA nor MDFA can be used as raw materials for making ALA; however, MDFA has a possibility of using bloating agent as an additive to raw materials of ALA. On the contrary of our expectation, CaO and other alkai components are not concentrated by the magnetic separation.…”
Section: Discussionmentioning
confidence: 80%
“…Far from the results in the case of using desulfurized bottom ash [6], it is concluded that neither DFA nor MDFA can be used as raw materials for making ALA; however, MDFA has a possibility of using bloating agent as an additive to raw materials of ALA. On the contrary of our expectation, CaO and other alkai components are not concentrated by the magnetic separation.…”
Section: Discussionmentioning
confidence: 80%
“…This is done electronically using beamforming algorithms without the involvement of the mechanical parts to steer the array [6][7][8][9][10]. The beamforming algorithms are classified mainly into three types: (1) estimating the Angle Of Arrival (AOA) algorithms like MUSIC and ESPRIT [9,[11][12][13], (2) non-blind algorithms where the transmitter and the receiver agree to certain code to detect the location of the transmitter to steer the main beam like Maximum Likelihood (ML), and Minimum Variance Distortionless Response (MVDR) [7], (3) blind beamforming algorithm. These algorithms are widely used and difficult to be built and developed.…”
Section: Introductionmentioning
confidence: 99%